ACUPRESSURE AND AROMATIC GINGER HERB FOR A MIGRAINE - Al ‘Amali, Mayla Khayra; Imandiri, Ario; Sukardiman, Sukardiman (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Migraine is a headache with pain attacks lasting 4 - 72 hours. Pain is usually unilateral, it is pulsating, the intensity of pain is moderate to severe and aggravated by activity, and can be accompanied by nausea, vomiting, photophobia, and phonophobia. Headaches are one of the most common disorders of the nervous system. It has been estimated that 47% of the adult population experience headaches at least once in the past year in general. According to TCM, headache is a disease with a headache accompanied by a variety of symptoms, where the cause is an external pathogen and causes in the body. Acupressure is one form of traditional treatment skills by suppressing acupuncture points with emphasis on using fingers or blunt objects on the surface of the body, in order to support promotive, effective, rehabilitative efforts. In addition to acupressure, herbal drinks can also be used to reduce pain, namely aromatic ginger. Purpose: Knowing the effect of acupressure and aromatic ginger herbs (Kaempferia galangal Linn.) combination therapy in reducing migraine complaints. Method: Acupressure at Fengchi point (GB20) 50 times, Taiyang (EX-HN5) 50 times, Sanyinjiao (SP6) 30 times, Taichong (LR3) 50 times and aromatic ginger herbs (Kaempferia galangal Linn.) 15 grams for 28 days. Result: Migraine complaints decreased from 5 times a month to 3 times a month. No more complaints of nausea, hypochondrium pain, diarrhea, and insomnia. Conclusion: Acupressure at Fengchi point (GB20) was 50 times of the pressure, Taiyang (EX-HN5) was 50 times of the pressure, Sanyinjiao (SP6) was 30 times of the pressure, Taichong (LR3) was 50 times of the pressure and the aromatic ginger herbs (Kaempferia galangal Linn.) As much as 15 grams for 28 days could reduce migraine complaints.